Modern and Postmodern Views of Education that Shape EFL Mentoring in the Teaching Practicum - Bonilla Medina, Sandra Ximena; Samacá Bohórquez, Yolanda (Colombian Applied Linguistics Journal, 2020)
Educational settings are now characterised by ethnic, cultural, linguistic, sociocultural and epistemological diversity. This article analyses epistemological diversity as an important factor in shaping teacher education programmes. This involved exploring how teacher-educators and student-teachers align themselves or negotiate modern and postmodern views of education. The research employed a narrative analysis-based on a qualitative methodology to discuss the effects of modern and postmodern views of knowledge construction and pedagogical action during the English Teaching practicum at a state university in Bogota. The findings suggest that, even though teacher-educators and student-teachers position themselves with discourses of generational change regarding conceptions of knowledge construction, there is a tendency to shape practices based on the ideals of fixed-defined generations (e.g. old, young) who have fixed views of education (old/traditional, young/contemporary) which consequently give particular shapes to pedagogical actions.